A STUDY OF THE USE OF THE MEDICINAL PLANTS IN TRADITIONAL MEDICINE AND THEIR EFFICACY - SANGEETA PRABHASKAR (International Journal of Multidisciplinary Research and Studies, 2020)
This is especially true in the developing nations of the world. In developing countries, a significant number of sick people utilize both contemporary medicine and traditional medicine in their treatment. Traditional medicines are typically less expensive than their contemporary counterparts, and they are most likely the only natural cures that are both readily available and easily accessible in the rural and isolated populations of poor nations. People who live in rural areas are more likely to take traditional medicines due to their close proximity to traditional healers and the fact that traditional healers understand both the rural residents’ culture and the environment in which they live as well as their patients. The pace at which medicinal plants are used across the world has been rising steadily over the past few centuries, particularly in less developed nations. This may largely be ascribed to the fact that medicinal plants are easily accessible, valued and acknowledged by a diverse range of societies, and thought to be free of risk while also being very effective. The estimated prevalence of the usage of medicinal herbs around the globe currently falls somewhere between the ranges of 50 and 95%.